Jeremy Thatcher, dragon hatcher - Coville, Bruce; Lippincott, Gary A. (Orlando, Fla. : Magic Carpet Books/Harcourt, 2007)
In a dark and eerie magic shop, Jeremy finds a multicolored ball containing a dragon--a tiny thing that speaks through mental telepathy. Soon, it will begin to grow, and grow, and grow.
"A magic shop book."
"Ages 8 to 12"--Cover p. [4].
Elem. School Library Collection
School Library Journal
Wilson's Children
4.9
Keywords: Dragons -- Juvenile fiction; Drawing -- Juvenile fiction; Friendship -- Juvenile fiction; Pets -- Juvenile fiction; Dragons -- Fiction; Drawing -- Fiction; Friendship -- Fiction; Pets -- Fiction; Size -- Fiction; Dragons -- Fiction; Drawing -- Fiction; Friendship -- Fiction; Pets -- Fiction; Size -- Fiction